PENGEMBANGAN BAHAN AJAR ENSIKLOPEDIA BERBASIS PENDEKATAN KONTEKSTUAL PADA PEMBELAJARAN IPA KELAS V SEKOLAH DASAR - Ramadhanti, Marsya Afifa; Zuliani, Rizki; Rini, Candra Puspita (STKIP Persada Khatulistiwa Sintang, 2025)
Teaching materials are a set of learning resources packaged in printed or non-printed form, containing a collection of information and content systematically organized to benefit both students and teachers in the learning process. This development research aims to explore the process of developing an encyclopedia-based teaching material specifically for Science (IPA) learning in Grade V at SDN 15 Kota Tangerang, as well as to determine the effectiveness and quality of the teaching materials based on validity and practicality aspects as evaluated by media experts, subject matter experts, educators, and student responses. The research method employed is the 4D Research and Development model, which consists of four stages: Define, Design, Develop, and Disseminate. The results of this research and development indicate that the validity score from media experts is 4.8, and from subject matter experts is 4.4—both falling under the category of